1996
DOI: 10.1046/j.1365-2249.1996.d01-847.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential clearance of glycoforms of IgG in normal and autoimmune-prone mice

Abstract: SUMMARYIn order to understand better the origins of the elevated levels of the glycoform of IgG that lacks galactose on both arms of the oligosaccharide chain (G0%) located in the Fc, which occurs in man and mouse with age, and in particular in autoimmune disease, we investigated the clearance of two glycosylated forms of IgG2a and IgG1 in normal (BALB/c) and autoimmune-prone (MRL/lpr, MRL/, and non-obese diabetic (NOD)) mice. To investigate the possibility of different rates of catabolism, enzymatically gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 31 publications
(44 reference statements)
2
34
0
Order By: Relevance
“…Early reports were conflicted regarding effects of glycosylation on antibody half-life, 18,[72][73][74][75] but our results support the most recent reports suggesting glycosylation does not affect FcRn-mediated PK. [66][67][68][69] In our study, this was confirmed by removing all N-glycosylation (only the natural germline Fc glycosylation site exists in the antibodies tested) and the in vitro FcRn binding measurement was used to compare the aglycosylated mAb to the naturally occurring glycosylated form produced in CHO cells.…”
Section: Discussionsupporting
confidence: 86%
“…Early reports were conflicted regarding effects of glycosylation on antibody half-life, 18,[72][73][74][75] but our results support the most recent reports suggesting glycosylation does not affect FcRn-mediated PK. [66][67][68][69] In our study, this was confirmed by removing all N-glycosylation (only the natural germline Fc glycosylation site exists in the antibodies tested) and the in vitro FcRn binding measurement was used to compare the aglycosylated mAb to the naturally occurring glycosylated form produced in CHO cells.…”
Section: Discussionsupporting
confidence: 86%
“…A high degree of galactosylation has been found to negatively affect IgG half-life in mice, 40 suggesting that galactosylation may also influence the transport of IgG from mother to child because both half-life and transport of IgG are mainly mediated by the neonatal Fc receptor FcRn. 41 However, no such skewing for IgG transport across the human placenta was found in our previous study, 42 in accordance with the fact that the Fc glycans are not involved in binding to FcRn.…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies have been described in literature to reduce blood clearance of targeting molecules. Most of these strategies focus on the enlargement of the targeting molecule above the critical size for renal clearance (60-70 kDa) by fusion to other proteins like albumin (30) and the Fc portion of an IgG (31) or by glycosylation (32) or pegylation (33). The use of bispecific antibodies as described herein, aiming a noncovalent association with albumin as a means to improve biodistribution and tumor deposition, was pioneered by Dennis et al from the Genentech labs (17).…”
Section: Discussionmentioning
confidence: 99%